PdII Dispersed on Magnetic Partially Reduced GO/OMWCNT Non‐Covalently Modified with a Vic‐Dioxime: An Efficient and Magnetically Retrievable Catalyst for Suzuki‐Miyaura Coupling Reaction. Issue 5 (3rd February 2021) - Shariatipour, Monire; Heydari, Akbar
Abstract: In the present study, a novel and magnetically separable Pd−catalyst system was designed using the immobilization of Pd II on Phendioxime(PDO)‐functionalized magnetic partially reduced (GO‐OMWCNT) composite (MPR (GO‐OMWCNT)/PDO/Pd II ). In the as‐obtained nanocomposites, the incorporation of 1D OMWCNTs and 2D graphene oxide can form a versatile 3D network with high specific surface area and synergic properties. Moreover, non‐ covalent phendioxime functionalization provides highly effective functional groups on the surface of MPR (GO‐OMWCNT) for Pd II . Non‐covalent interaction carries out through π‐π stacking and hydrogen bond interactions .The catalytic activity of this nanocomposite was examined in the Suzuki–Miyaura cross‐coupling reaction. MPR (GO‐OMWCNT)/PDO/Pd II composite exhibited good catalytic efficiency and obtained the products in good to excellent yield under mild aerobic conditions. Moreover, the suggested catalyst could be easily recovered magnetically and used for at least six runs without a noticeable decrease in its catalytic activity. Abstract : A novel and efficient protocol for Suzuki‐ Miyaura reaction using magnetically separable v ic‐oxime‐functionalized magnetic partially reduced (GO‐OMWCNT) decorated with palladium (II) was developed.